Aspartame and ischemic stroke: unraveling the molecular link through network toxicology and molecular docking analysis - Tianyu Zhang; Tao Wang; Kuangyang Yu; Changren huang; Kunyang Bao (Scientific Reports)
Abstract Aspartame, a widely used artificial sweetener, remains controversial due to neurotoxic risks from its metabolites—phenylalanine, aspartic acid, and methanol. While epidemiological studies link artificial sweeteners to cerebrovascular disease, the molecular mechanisms connecting aspartame to ischemic stroke are unclear. This study integrates network toxicology and molecular docking to identify key targets and pathways. Potential aspartame targets were predicted using STITCH, SwissTargetPrediction, and SEA databases, while ischemic stroke-related genes were retrieved from GeneCards, OMIM, and TTD. Venn analysis identified 201 overlapping genes, with IL1B, MMP9, SRC, AGT, and TNF as core targets. GO/KEGG enrichment revealed their roles in the renin-angiotensin system, complement/coagulation cascades, and inflammatory pathways. Molecular docking demonstrated strong binding affinities between aspartame and these targets, suggesting direct modulation. Our integrated analysis suggests that aspartame may contribute to ischemic brain injury through multi-target interactions, potentially disrupting inflammatory responses and vascular homeostasis. This study provides preliminary systematic insights into the potential neurotoxicity mechanisms of aspartame, offering insights for food additive safety evaluation and stroke prevention. Further validation is required to clarify metabolite synergies and dose–response relationships.